Changes in retinal vessels related to varicocele: a pilot investigation. (28th August 2015) - Coşkun, M.; Ilhan, N.; Elbeyli, A.; Rifaioğlu, M. M.; Inci, M.; Davran, R.; Tuzcu, E. A.; Yarbağ, A.; Davarci, M.; Gökçe, A.
Summary: The aim of this study was to investigate whether retinal vasculature changes had occurred (retinal artery diameter, retinal vein diameter and artery/vein ratio) in patients with varicocele. This pilot study included 50 healthy subjects with any eye disease apart from slight refractive errors and 55 patients with varicocele. Retinal arteriolar and venular diameters were measured and summarised as central retinal arteriolar equivalent (CRAE) and central retinal venular equivalent (CRVE). Retinal microvascular diameters and the arteriolar–to‐venular ratio (AVR) were assessed with a digital retinal camera. All measurements and calculations were performed using a computer‐based program. The mean CRAE value was 151.8 ± 3.6 μm in the study group and 150.4 ± 4.5 μm in the control group. Mean CRVE value was 209.4 ± 5.9 μm in the study group and 200.1 ± 8.7 μm in the control group. AVR was found 0.72 ± 0.02 in the study group and 0.75 ± 0.03 in the control group. There were significant differences between groups in terms of CRVE and AVR. There were no significant differences between groups in terms of CRAE. The results of this study showed that the patients with varicocele showed significant changes on retinal vascular diameter.